Representation of the Concept “Loneliness” in Katherine Mansfield’s Authorial World Picture - Sargsyan, Mariana; Madoyan, Gohar (Armenian Folia Anglistika, 2015)
The present paper aims at observing the peculiarities of the linguistic representation of the concept loneliness in K. Mansfield’s authorial world picture. The authorial approach to the representation of the mentioned concept is studied in phonetic, lexical and syntactic aspects with the aim of discovering the specificities of interaction at micro and macro-levels of the text. A preliminary overview of the linguistic representation of the concept loneliness provided by the research will enable linking the results of the study with the cognitive stylistic individuality of the author.
Keywords: concept “loneliness”; authorial world picture; micro- and macro-structure of the text